FEMALE SALESIAN SCHOOL INSTITUTIONS AND EDUCATIONAL, SOCIAL AND CULTURAL PRACTICES IN THE SOUTH OF OLD MATO GROSSO - Olmo, Roselaine Alves; Andrade, Heloise Vargas de (Horizontes - Revista de Educação, 2025)
The aim of this article is to understand the educational, cultural and social practices that constituted the dispositions of the female gender habitus provided to girls who studied at secondary schools in Salesian girls' schools in the south of the former Mato Grosso, from 1942 to 1961. The theoretical contribution of Pierre Bourdieu and interlocutors was used. The results show that the school institutions structured a female gender habitus based on educational practices such as: the Preventive System, school subjects, the "Literary Guild", which allowed students to take part in music rehearsal classes, theater rehearsals and encouraged literature by classical authors, parades, graduation ceremonies and other festivities.